Traditionally feminine hobbies and engineering aptitudes - Peters, Diane; Lucietto, Anne (Frontiers in Education, 2024)
In the past, there was a widely held belief that women lacked the aptitude for STEM careers, including engineering. Activities traditionally associated with women were perceived as less technical and rigorous than those associated with men. "Masculine" hobbies like woodworking and metalworking were seen as good preparation for engineering. In contrast, traditionally feminine hobbies like sewing, quilting, and knitting were considered preparation for homemaking. However, many traditionally feminine crafts require and develop mathematical knowledge and technical aptitudes, which are essential for success in engineering.This paper explores parallels between traditionally feminine crafts and technical aptitude. By analyzing information from various sources, including books and magazines related to these crafts, we demonstrate how these activities can develop technical aptitudes and explain this in the context of career theory, which is fundamental in comprehending how individuals navigate their professional paths. Childhood, early adult, and later experiences, such as engaging in craft and hobby activities, can significantly impact skill development that carries over into other phases of life. According to career construction theory, individuals actively shape their careers through various self-regulatory competencies [1]. This theory posits that career adaptability, a key competency, can enhance job crafting behaviors, ultimately increasing work engagement [1].By understanding how these activities can enhance technical aptitudes, the engineering community can better identify and support individuals who may have a natural inclination for engineering, broadening our perception of what engineering aptitude looks like and encouraging individuals from diverse backgrounds, including a greater proportion of women, to pursue engineering careers.